Effect of peripheral vision training on the attack of beginner indoor soccer players: a study during competition - Nelson Kautzner Marques Junior (Universidade Federal de Santa Catarina, 2009)
This study was conducted within the context of Human Motor Skill Science, in the area of Biophysical Dimension and following the research line of the Study of Learning Mechanisms and Processes and of Motor Conduct within the epistemological construct of phenomenological explanation. The objective of this study was to investigate peripheral vision training (PVT) and its effect on attack runs during indoor soccer, taking into account dominant laterality (brain hemisphere function) in both learning speed andoffensive skills. Ten beginner indoor soccer players aged 10.4 ± 2.31 years, from Lar da Criança Padre Franz Neumair, Ititioca, Niterói, Rio de Janeiro, Brazil, participated in the study. The boys were divided into an experimental group (EG, n = 5) and a controlgroup (CG, n = 5) with similar dominant laterality (brain hemisphere function) (H) (EG: 80% left H and 20% right H, CG: 60% left H and 40% right H). The players underwent nine training sessions, followed by a championship, and then six additional sessions, followed by a second championship. Each championship was filmed for scoutvideo analysis. Two-way ANOVA revealed a significant difference in peripheral vision during offensive runs between CG and EG, with marked acquisition of peripheral vision in EG. The quality of the attack runs was significant (two-way ANOVA). EG was the better team at the beginning of the attack runs and during attack development, whereas CG was better at attack finalization during the first championship. EG showed more competence in attack run finalization during the second championship. No significant difference in the number of goals scored was observed between the two groups (two-wayANOVA, p>0.05). The frequency of participation in the training sessions was significant (t-test for independent samples, p≤0.05), with EG attending more sessions. In conclusion, EG acquired peripheral vision, a finding suggesting that PVT improves the attack capacity of indoor soccer players.